Impaired neutralizing antibody activity against B.1.617.2 (delta) after anti-SARS-CoV-2 vaccination in patients receiving anti-CD20 therapy - Töllner, Maximilian; Speer, Claudius; Benning, Louise; Bartenschlager, Marie; Nußhag, Christian; Morath, Christian; Zeier, Martin; Süsal, Caner; Schnitzler, Paul; Schmitt, Wilhelm; Bergner, Raoul; Bartenschlager, Ralf; et al. (Journal of Clinical Medicine, 2022)
Background: To characterize humoral response after standard anti-SARS-CoV-2 vaccination in Rituximab-treated patients and to determine the optimal time point after last Rituximab treatment for appropriate immunization. Methods: Sixty-four patients who received Rituximab within the last seven years prior to the first anti-SARS-CoV-2 vaccination were recruited in a prospective observational study. Anti-S1 IgG, SARS-CoV-2 specific neutralization, and various SARS-CoV-2 target antibodies were determined. A live virus assay was used to assess neutralizing antibody activity against B.1.617.2 (delta). In Rituximab-treated patients, CD19+ peripheral B-cells were quantified using flow cytometry. Results: After second vaccination, all antibodies were significantly reduced compared to healthy controls. Neutralizing antibody activity against B.1.617.2 (delta) was detectable with a median (IQR) ID50 of 0 (0-1:20) compared to 1:320 (1:160-1:320) in healthy controls (for all p < 0.001). Longer time period since last Rituximab administration correlated with higher anti-SARS-CoV-2 antibody levels and a stronger neutralization of B.1.617.2 (delta). With one exception, only patients with a CD19+ cell proportion ≥ 1% had detectable neutralizing antibodies. Conclusion: Our data indicate that a reconstitution of the B-cell population to >1% seems crucial in developing neutralizing antibodies against SARS-CoV-2. We suggest that anti-SARS-CoV-2 vaccination should be administered at least 8-12 months after the last Rituximab treatment for sufficient humoral responses.